Connecting to Compete 2012 : Trade Logistics in the Global Economy - Arvis, Jean-François; Mustra, Monica Alina; Ojala, Lauri; Shepherd, Ben; Saslavsky, Daniel (World Bank, Washington, DC, 2013)
This is the third edition of connecting to compete: trade logistics in the global economy. At its heart is the Logistics Performance Index (LPI), which the World Bank has produced every two years since 2007. The LPI measures on-the-ground trade logistics performance this year, in 155 countries helping national leaders, key policymakers, and private sector traders understand the challenges they and their trading partners face in reducing logistical barriers to international commerce. Logistics, organizing the movement of goods over time and space, has evolved from its 19th century military roots to today's international supply chains. As the backbone of international trade, logistics encompasses freight transportation, warehousing, border clearance, payment systems, and many other functions. These functions are performed mostly by private service providers for private traders and owners of goods, but logistics is also important for the public policies of national governments and regional and international organizations. The LPI provides a simple, global benchmark to measure logistics performance, filling gaps in datasets by providing systematic, cross-country comparisons. A joint venture of the World Bank, logistics service providers, and academics, the LPI is built around a survey of logistics professionals. By asking freight forwarders to rate countries on key logistics issues such as customs clearance efficiency, infrastructure quality, and the ability to track cargo it captures a broad set of elements that affect perceptions of the efficiency of trade logistics in practice.